Autism and understanding : the Waldon approach to child development - Solomon, Walter; Holland, Chris, 1940-; Middleton, Mary Jo. (London : SAGE, 2012)
'This book does not offer a'miracle cure' for autism, although the authors aim to counteract the prevailing view that autism is a lifetime condition. Authors Walter Solomon, Chris Holland and Mary Jo Middleton demonstrate that with the appropriate intervention, children with autism - and other special needs - can gain a fuller understanding of the world and learn to take a constructive and contributing place in it. The authors set out an approach based on Dr. Geoffrey Waldon's philosophy of the development of understanding, which centers on helping children learn how to learn. The Waldon Approach is presented through accounts of how it has helped to enrich many lives.'--Publisher's website.
Includes bibliographical references (p. [213]-216) and index.
Keywords: Waldon, Geoffrey; Autistic children -- Education